MULTICULTURAL ISLAMIC EDUCATION VALUES IN THE INTERACTION OF SANTRI WITH CHINESE COMMUNITIES - Moh Sholihuddin (Universitas Islam Malang, 2021)
The Islamic boarding school is the oldest educational institution in Indonesia, as well as Kauman islamic boarding school of Lasem which founded in 2003. It is located in a multicultural environment, which peacefully coexists between people of different races, ethnicities and beliefs. This research aims to determine the values â€‹â€‹of multicultural Islamic education that are resulted of the interaction of santri with Chinese communities. The approach used in this research is a qualitative approach with a phenomenological study. The data collection techniques were carried out by depth interview, observation and document analysis. Data analysis techniques used the Creswell phenomenological data analysis model, which includes; describing the phenomenon / experience that will be used as data, compiling a list of important statements to be grouped into important units or themes (data collection), writing textual descriptions (about â€œwhatâ€) and structural descriptions (about â€œhowâ€), combining the two descriptions for compiled into a report. The results of this research are: the values â€‹â€‹of multicultural Islamic education resulted of the interaction of santri with the Chinese community at Kauman Islamic boarding school of Lasem are adaptation, syafaqoh or compassion and caring.